If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(7-4x)=18
We move all terms to the left:
2(7-4x)-(18)=0
We add all the numbers together, and all the variables
2(-4x+7)-18=0
We multiply parentheses
-8x+14-18=0
We add all the numbers together, and all the variables
-8x-4=0
We move all terms containing x to the left, all other terms to the right
-8x=4
x=4/-8
x=-1/2
| (3x-2)(x)=28 | | 6(u-6)-8u=-26 | | 6y-103=71 | | m+16−28=5 | | 12x2-32x+5=0 | | 4.6+10m=8.84 | | 9x-13=13x | | X²+10x+19=0 | | 225=27x−18 | | 3x-15=108 | | 4x-10+x=5 | | r-17.1=-14.8 | | 5p-10=9 | | -9=4x-1+4 | | 75x+5=45 | | -1=-2a+a | | K3k=15 | | 2/3+3x=83/3 | | -2-3y+8=-5y-12 | | k-87=-33 | | k−87=-33 | | x+1/2=1/4 | | m-6-6=9(m-8)-(m+3) | | x/20-7=3 | | 34/g=−12 | | 4^2-22s+10=0 | | -3(x-5)=-(x-9) | | 5t-13=3t | | 2/7(y-28)=-14 | | 42+10n=-3(1-5n) | | (x+3)^2=x^2+-3(1+-x) | | z-2,3=4.7 |